“Under the subtle wreath”: Louise Bogan, Felicia Hemans, and Petrarchan Poetics - Sweet, Nanora (Romanticism on the Net, 2003)
AbstractLouise Bogan joked that in a former life she had been “Felicia Hemans.” A lush Romantic and an austere Modernist, Hemans and Bogan appear polar opposites, yet these learned women poets shared a laureate poetics of Love and Fame. Hemans alludes directly to Petrarch’s laureate triumph in “The Magic Glass”; in poetry and prose she portrays the difficult laureateships of Sappho and Tasso. Both Hemans and Bogan seemed laureates to their contemporaries and successors, yet both found laurels an ambiguous donnée, Bogan a “burden” among flowers, Hemans a fiery crown for the likes of “the Bride of the Greek Isle.” Petrarch gained his laurels in a formal triumph at Rome, a scene mandating abjuration and entailing defeat. His I trionfi enacted triumph and its reversals in a sequence mounting from Love to Chastity, Death, Fame, Time, and Eternity. Bogan’s laurels were similarly fugual, a “subtle wreath” combining “the line of feeling” of “sentimental” women’s poetry with “the line of thought” in masculine Metaphysical Modernism. The poems of Bogan and Hemans that most vex critics – Bogan’s life-denying “Henceforth, from the Mind,” Hemans’s fame-abjuring “Corinne at the Capitol” – read differently as Petrarchan triumphs, that is, as abjurations signaling fresh triumphs to come.